Characterization of Monoclonal Antibodies Recognizing Citrulline-Modified Residues - Chen, Yaqiong; Weng, Lin; Liu, Wei; Deng, Chenxi; Xuan, Jinxiu; Ma, Yuan; Li, Cao; Jiang, Jinlu; Chen, Juan; Ge, Shengxiang (Frontiers in Immunology, 2022)
Background: Citrullination is a post-translational protein modification linked to the occurrence and development of a variety of diseases. The detection of citrullinated proteins is predominately based on antibody detection although currently available reagents demonstrate detection bias according to the environmental context of the citrullinated residues. This study aimed to develop improved antibody reagents capable of detecting citrullinated residues in proteins in an unbiased manner. Methods: BALB/c mice were sequentially immunized using citrulline conjugates with different carrier proteins, and specific monoclonal antibodies (mAbs) identified by primary screening using citrulline-conjugated proteins unrelated to the immunogen. Secondary screening was performed to identify mAbs whose reactivity could be specifically blocked by free citrulline, followed by identification and performance assessment. Results: Two mAbs, 22F1 and 30G2, specifically recognizing a single citrulline residue were screened from 22 mAbs reacting with citrulline conjugates. Compared with commercially available anti-citrulline antibodies (AB6464, AB100932 and MABN328), 22F1 and 30G2 demonstrated significantly higher reactivity as well as a broader detection spectrum against different citrullinated proteins. 22F1 and 30G2 also had higher specificity than commercial antibodies and overall better applicability to a range of different immunoassays. Conclusion: Two mAbs specifically recognizing a single citrulline residue were successfully produced, each possessing good specificity against different citrullinated proteins. The improved utility of these reagents is expected to make a strong contribution to protein citrullination-related research.